2006
DOI: 10.1016/j.jmb.2005.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Model for RNA Binding and the Catalytic Site of the RNase Kid of the Bacterial parD Toxin–Antitoxin System

Abstract: The toxin Kid and antitoxin Kis are encoded by the parD operon of Escherichia coli plasmid R1. Kid and its chromosomal homologues MazF and ChpBK have been shown to inhibit protein synthesis in cell extracts and to act as ribosome-independent endoribonucleases in vitro. Kid cleaves RNA preferentially at the 5 0 side of the A residue in the nucleotide sequence 5 0 -UA(A/C)-3 0 of single-stranded regions. Here, we show that RNA cleavage by Kid yields two fragments with a 2 0 :3 0 -cyclic phosphate group and a fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(101 citation statements)
references
References 54 publications
3
98
0
Order By: Relevance
“…As discussed below, mazEF and homologous systems (parD and chpB) have been most extensively studied on their plasmid and chromosomal origins in enterobacteria (34)(35)(36). Because 100% of the VRE strains obtained for this study harbored genes for a plasmidencoded mazEF TA system (Fig.…”
Section: Presence Of Ta Genes On Plasmids That Have Vancomycin-resistmentioning
confidence: 99%
“…As discussed below, mazEF and homologous systems (parD and chpB) have been most extensively studied on their plasmid and chromosomal origins in enterobacteria (34)(35)(36). Because 100% of the VRE strains obtained for this study harbored genes for a plasmidencoded mazEF TA system (Fig.…”
Section: Presence Of Ta Genes On Plasmids That Have Vancomycin-resistmentioning
confidence: 99%
“…7C). ToxN enzymes are proposed to cleave their substrates through a metal-independent RNase T1-like mechanism, based on their active-site architectures, the presence of the 2′-3′-cyclic phosphate product in the active site, and their structural homology to Kid, whose reaction mechanism has been studied in detail (21,25). The RNA fragment patterns produced by ToxN Pa degradation in vitro (Fig.…”
mentioning
confidence: 99%
“…In this case, the complex formation was in the fast exchange regime. NMR titration experiments indicated that one dimer binds a single RNA molecule and the stoichiometry of the complex was further confirmed by native mass spectrometry [47]. The RNA binding protein RsmE also folds into a symmetrical homodimer [157,158].…”
Section: Nmr Titration Experiments Are Crucial Steps For Defining a "mentioning
confidence: 81%
“…Of these structures, 52 were determined using classical NMR methodology (Fig. 1) and two consist of structural models generated by docking using sparse NMR data [46,47]. This results in an estimated weight for the contribution of NMR in the structure elucidation of protein-RNA complexes to approach 40%.…”
Section: Introductionmentioning
confidence: 99%